Characterization of antiplatelet response to low‐dose cangrelor utilizing platelet function testing in neuroendovascular patients. Issue 10 (18th September 2021) - Holden, Devin N.; Entezami, Pouya; Bush, Maximilian C.; Field, Nicholas C.; Paul, Alexandra R.; Boulos, Alan S.; Yamamoto, Junichi; Dalfino, John C.
Abstract: Study Objectives: The optimal antiplatelet therapy for emergent neuroendovascular stenting is uncertain. Cangrelor is an intravenous P2Y12 inhibitor that is an attractive option due its favorable pharmacokinetic profile and ease of measurability but optimal dosing remains unclear. The primary objective of this study is to characterize the dose response of low dose cangrelor (<2 mcg/kg/min) with the utilization of platelet function testing (PFT). Design: A retrospective review of all patients treated with cangrelor for either procedural stenting or bridging was conducted between January 1st, 2019 and October 31st, 2020. Seventy‐two patients met inclusion criteria. An in‐depth analysis of dose response to low dose cangrelor based on PFT was performed. Patients: Neuroendovascular patients treated with cangrelor. Setting: Albany Medical Center Hospital. Intervention and Main Results: Patients who underwent procedural stenting were given a bolus of 5 mcg/kg and an initial infusion rate of either 0.75 mcg/kg/min or 1 mcg/kg/min. Patients who were bridged with cangrelor were administered an initial infusion rate of 0.75 mcg/kg/min or 1 mcg/kg/min. Twelve patient's doses were titrated to achieve a platelet reactivity unit (PRU) between 50–150; three patient's doses were titrated multiple times. Based on initial PFT results, utilizing the 1 mcg/kg/min maintenance dose resulted in more patients being in the acceptable (10–180) and desired (50–150) PRU range than the 0.75 mcg/kg/min dose (47% vs 56% and 70% vs 80%, respectively). Final recorded PRU results showed that 64% of patients had PRUs in the optimal range (50–150) and 88% of patients had PRUs in the desire range (10–180). Conclusions: Utilizing low doses of cangrelor with platelet function testing is an option during emergent neuroendovascular stenting and bridging. Cangrelor demonstrates significant variability in response at low doses and exhibits a dose response relationship when PFT is utilized.